2010
DOI: 10.1111/j.1365-2923.2009.03570.x
|View full text |Cite
|
Sign up to set email alerts
|

Identifying challenges for academic leadership in medical universities in Iran

Abstract: CONTEXT The crucial role of academic leadership in the success of higher education institutions is well documented. Medical education in Iran has been integrated into the health care system through a complex organisational change. This has called into question the current academic leadership, making Iranian medical universities and schools a good case for exploring the challenges of academic leadership. OBJECTIVES This study explores the leadership challenges perceived by academic managers in medical schools a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 34 publications
2
23
0
Order By: Relevance
“…HCOs, especially in low- and middle-income countries, are one of the institutions with the highest bureaucracy and the least effective management in the public sector. They have changed into highly centralized and hierarchical bureaucracies and have partial and boring executive rules, with permanent staff working in these institutions ( 39 , 51 ). Existence of numerous professionals in the hospitals that require specialized knowledge and skills makes the organization more complicated because people’s different positions retard the communication and makes it difficult to coordinate people and processes.…”
Section: Discussionmentioning
confidence: 99%
“…HCOs, especially in low- and middle-income countries, are one of the institutions with the highest bureaucracy and the least effective management in the public sector. They have changed into highly centralized and hierarchical bureaucracies and have partial and boring executive rules, with permanent staff working in these institutions ( 39 , 51 ). Existence of numerous professionals in the hospitals that require specialized knowledge and skills makes the organization more complicated because people’s different positions retard the communication and makes it difficult to coordinate people and processes.…”
Section: Discussionmentioning
confidence: 99%
“…The crucial role of leadership in medical education is well documented [ 25 , 26 ]. Although academic leadership faces challenges (as organizational issues, mismatch between authority and responsibilities, a boss-centred culture and low motivation [ 26 ], students find in Academic Leagues an important scenario of learning and practice. The management of AL is elected amongst student members each year.…”
Section: Discussionmentioning
confidence: 99%
“…In a successful educational institute the limit of authorities, responsibilities, policies, regulations, and strategic or operational programs are clear and at the hands of beneficiaries. The results of Bikmoradi et al (2010) study on the challenges of scientific management in the medical universities showed that scientific management in medical universities is very inefficient and the majority of components of management structure are uncertain and ambiguous ( Bikmoradi et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%